TINGKAT KECEMASAN BAGI LANSIA YANG MEMILIKI PENYAKIT PENYERTA DITENGAH SITUASI PANDEMIK COVID-19 DI KECAMATAN PARONGPONG, BANDUNG BARAT - Lumban Tobing, Clark Pangapuli Reinhart; Wulandari, Imanuel Sri Mei (Coping: Community of Publishing in Nursing; Vol 9 No 2 (2021): April 2021DO - 10.24843/coping.2021.v09.i02.p02, 2021)
Elderly people, especially those who have comorbidities such as hypertension, heart disease and diabetes mellitus experience anxiety caused by the pandemic of COVID-19. The COVID-19 pandemic condition will certainly increase the level of anxiety experienced by the elderly with comorbidities. This study aims to determine the level of anxiety experienced by elderly people with comorbidities in the pandemic situation in Parongpong District, West Bandung Regency. The method used in this research is descriptive quantitative method with purposive sampling. The sample provisions were elderly (age 60 years and over) with comorbid diseases (heart disease, hypertension, diabetes mellitus). Data collection uses a questionnaire and informed consent in collaboration with the Parongpong Community Health Center and the clinic of Adventist University of Indonesia in the Parongpong sub-district by following the health protocol. The results indicates at that the level of anxiety experienced by the elderly with comorbid diseases (comorbid) is very severe with an anxiety level scale of 30.35. Elderly people with hypertension experience a very severe level of anxiety with an anxiety level scale of 31.43, people with heart disease experience a severe level of anxiety with an anxiety level scale of 29.41, and people with diabetes mellitus experience a severe level of anxiety with an anxiety level scale of 29.67.